THEORETICAL FOUNDATIONS OF METAPHOR AND PRAGMATICS (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
This comprehensive article explores the intricate intersection of metaphor and pragmatics, offering an in-depth analysis of their theoretical foundations, historical evolution, and functional roles within human communication.  The paper examines the generation, decoding, and contextual application of metaphorical expressions through the frameworks of leading pragmatic theories. Ultimately, the research highlights the indispensable role of context, speaker intention, and shared cognitive environments in deriving meaning from non-literal language.